Toward the Transition State Structure of AlkA-Catalyzed N-Glycoside Hydrolysis using Kinetic Isotope Effects - Ramnarine, Amanda (My University, 2008)
AlkA is a monofunctional DNA glycosylase from E.coli. This enzyme catalyzes the hydrolysis of the N-glycosidic bond, initiating the first step in the base excision repair pathway. This activity is crucial to the maintenance of the genetic code, as the persistence of DNA aberrations can have significant cellular consequences including mutation, and inhibition of DNA replication and transcription. This enzyme has a broad substrate specificity catalyzing the excision of various lesions (including alkylation, oxidation and deamination products) from DNA. While biochemical and structural studies have been carried out on AlkA; how this enzyme is able to recognize and excise a variety of structurally diverse lesions from DNA and the mechanism by which this excision occurs remains unknown. In this study we have shown that a stem-loop DNA structure containing a hypoxanthine bulge is an optimal substrate for TS analysis of AlkA-catalyzed N-glycoside hydrolysis. In addition, we have developed methods to synthesize radiolabeled deoxyinosine triphosphate (diTP) and incorporate this radiolabeled nucleotide into the stem-loop DNA structure. We have developed a facile method of purification for his-tagged AlkA and his-tagged AlkA containing a TEV protease recognition site (for removal of the his-tag), and have shown that these proteins display an activity similar to that of wild-type AlkA. The [1'-3H] KIE was measured using liquid scintillation in a proof-of-principle experiment. The observed value of 1.046 is indicative of either a relatively synchronous ANDN (SN2) TS or an early DN*AN (SN1) TS with oxacarbenium ion character in the sugar ring, but significant bond order to the leaving group base still remaining. Future work involves repeat measurements of the [1 '-3H] KIE to validate the accuracy of the measurement observed here, examination of commitment to catalysis and optimization of the hypoxanthine bulge substrate synthesis. Analysis of KIEs at additional sites on the hypoxanthine base and sugar ring will contribute to TS analysis of AlkA-catalyzed N-glycoside hydrolysis and help elucidate the mechanism of hydrolysis.
Keywords: transition state; AlkA-Catalyzed; N-Glycoside; hydrolysis; kinetic isotope